Hepatitis E: Diagnostic and Therapeutic Challenges - Mohammad K Parvez (Archives of Hepatitis Research - Peertechz Publications, 2017)
Hepatitis E virus (HEV) is a globally important water and foodborne pathogen of acute and chronic hepatitis E [1,2]. HEV infection may be symptomatic or asymptomatic that has affected about one-third of world population with a case fatality rate of 1-2%, including 20-30% of infected pregnant women [3-5]. Though inherently hepatotropic causing fulminant liver failure and cirrhosis, HEV has recently evolved with extra hepatic manifestations where biochemical/serological evidence of infection is often modest or absent [6-8].